2019
DOI: 10.1038/s41588-019-0507-7
|View full text |Cite
|
Sign up to set email alerts
|

The genomic landscape of metastatic breast cancer highlights changes in mutation and signature frequencies

Abstract: Whole genome sequencing (WGS) of prospectively collected tissue biopsies of 442 metastatic breast cancer (mBC) patients reveals that, compared to primary BC, tumour mutational burden (TMB) doubled, relative contributions of mutational signatures shifted, and mutation frequency of six known driver genes increased in mBC. Significant associations with pre-treatment were observed as well. The contribution of mutational signature 17 was significantly enriched in patients pre-treated with 5-FU, taxanes, platinum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
254
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(272 citation statements)
references
References 49 publications
15
254
1
2
Order By: Relevance
“…[3][4][5] In addition, tumours evolve over time and treatments while developing drug-resistance mechanisms. 6 From these observations emerge the importance of a biopsy that could provide clinicians with realtime data to facilitate treatment decision-making. In theory, subsequent collections of solid biopsies from multiple sites could be a solution; however, in practice, not all sites are accessible by surgery and such a procedure is highly invasive leading to patient discomfort and health complications.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In addition, tumours evolve over time and treatments while developing drug-resistance mechanisms. 6 From these observations emerge the importance of a biopsy that could provide clinicians with realtime data to facilitate treatment decision-making. In theory, subsequent collections of solid biopsies from multiple sites could be a solution; however, in practice, not all sites are accessible by surgery and such a procedure is highly invasive leading to patient discomfort and health complications.…”
Section: Introductionmentioning
confidence: 99%
“…Patients do not die from their primary breast tumor but as a consequence of metastases. Due to tumor evolution and treatment pressure, the genomic alterations in metastatic BC can differ substantially from the primary tumor [79]. To date, the molecular and microenvironmental determinants of metastasis are largely unknown, as is the timing of systemic spread, hindering effective treatment and prevention efforts [13, 68, 80].…”
Section: Resultsmentioning
confidence: 99%
“…Last, our cohort of patients might have a different genomic make-up in metastases than that in primary breast cancer, as shown by the in silico analyses. In that respect, Angus et al (2019) have recently reported on the genomic landscape of MBC and showed more frequent mutations in ESR1, TP53, NF1, AKT1, KMT2C and PTEN in ER+/HER2-metastatic lesions than in primary breast carcinomas. Our targeted assay evaluated three of these genes (ESR1, TP53 and AKT1).…”
Section: Discussionmentioning
confidence: 99%